Unions and compensating wage differentials for workplace accident risk: the English and Welsh railway industry, 1902–12 † - Anderson, Peter (Blackwell Publishing Ltd, 2021)
The effect of unions on workers’ wage premiums for accepting on-the-job accident risk is a prominent subset of compensating differentials research. This article contributes to the literature by using a newly-constructed balanced panel of railwaymen working in the traffic departments of three prominent Edwardian railway companies with operations in England and Wales. It avoids previous issues of endogeneity by controlling for a number of variables correlated with the risk rates, notably individual fixed effects. The results show that the largest railway union of the time, the Amalgamated Society of Railway Servants, was able to transform growing union density into power that increased wage premiums for fatal accident risk, although railwaymen's wages did not compensate them for non-fatal accident risk. This article also considers how this relationship differed by varying levels of company-specific human capital as measured by tenure. It finds a non-linear relationship for both risk rates across the tenure cohorts.